Response to Preoperative Therapy in Localized Pancreatic Cancer - Perri, Giampaolo; Prakash, Laura R.; Katz, Matthew H. G. (Frontiers in Oncology, 2020)
Evaluation of response to preoperative therapy for patients with pancreatic adenocarcinoma has been historically difficult. Therefore, preoperative regimens have generally been selected on the basis of baseline data such as radiographic stage and serum CA 19-9 level and then typically administered for a pre-specified duration as long as 6 months or more. The decision to proceed with resection following preoperative therapy likewise has rested upon the absence of disease progression rather than evidence for tumor response. This article reviews the basis for the evaluation of therapeutic response after preoperative therapy for pancreatic cancer in the existing scientific literature, and providing updates and new perspectives.